Implementing an online course in the MOOC environment with a focus on science and mathematics education - Kazakova, Julia; Shastina, Elena; Gibadulina, Ilzira (Institute of Advanced Engineering and Science, 2024)
The study focused on the development and evaluation of an online course in the massive open online courses (MOOC) environment, specifically targeting science and mathematics education. The goal was to utilize pedagogical design principles, particularly those derived from the analysis, design, development, implementation, and evaluation (ADDIE) model, to create an effective learning experience for students in different years of study. The online course was hosted on the edX platform, which is a popular platform for MOOCs. The assessment of the online course covered various criteria: interface, interaction, and design. The criteria of interface, interaction, and design received high marks from students of the two groups. The study found that the participants were highly engaged during the training, which is a positive outcome. The analysis of interest in online learning among first- and fourth-year students shows that first-year students had an average level of interest in online learning of 4.50 with a standard deviation of 0.32. Fourth-year students had an average level of interest of 4.45 with a slightly larger standard deviation of 0.41. Student engagement is an important factor in effective learning, as it reflects their active involvement and motivation in the learning process.